1986
DOI: 10.7164/antibiotics.39.978
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of bacteria to serum lysis or phagocytosis following growth in subinhibitory levels of lincosaminide or spectinomycin related antibiotics.

Abstract: The effects of subinhibitory concentrations of antibiotics on polymorphonuclear leukocyte (PML) and serum killing of Staphylococcus aureus 502A (UC 9116) and Escherichia coli UC 9451 were studied. Exposure of these bacteria to subinhibitory levels of certain lincosaminides, spectinomycin, or 6'-n-propylspectinomycin altered their susceptibility to these host defense mechanisms, while exposure to gentamicin had no effect. However, each organism responded differently to treatment with the antibiotics.S. arrreus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Interestingly, the mechanism of pirlimycin action is that it increases the susceptibility of the pathogen to phagocytosis by polymorphonuclear leukocytes after exposure to sub‐inhibitory concentrations (Cialdella et al . ). Whittem () reported that intramammary infusion induces a rapid increase in the MIC of microorganisms isolated from the mammary glands of dairy heifers.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, the mechanism of pirlimycin action is that it increases the susceptibility of the pathogen to phagocytosis by polymorphonuclear leukocytes after exposure to sub‐inhibitory concentrations (Cialdella et al . ). Whittem () reported that intramammary infusion induces a rapid increase in the MIC of microorganisms isolated from the mammary glands of dairy heifers.…”
Section: Resultsmentioning
confidence: 97%
“…It has activity against some pathogens which cause bovine mastitis including Staphylococcus aureus ( Owens et al ., 1993a ; Watts & Salmon, 1997), Staphylococcus spp., many streptococci ( Thornsberry et al ., 1993 ) and some entero‐cocci ( Thornsberry et al ., 1993 ; Watts et al ., 1995 ). Pirlimycin exhibits a post antibiotic effect in vitro against Staphylococcus aureus isolated from bovine mastitis ( Owens et al ., 1993b ) and causes increased susceptibility of the pathogen to phagocytosis by polymorphonuclear leukocytes after exposure to subinhibitory concentrations of the antibiotic ( Cialdella et al ., 1986 ). Many species of anaerobic bacterial pathogens are extremely sensitive to pirlimycin ( Qadri et al ., 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lincomycin induced a nonsignificant increase in phagocytic activity and index (Fateeva 1983) and (Faden et al 1985). Furthermore, lincosamides have dramatically increased phagocytic activity (Cialdella et al 1986) as well as achieves high intracellular levels of phagocytic cells (Alikhani & Salehifar 2012). Our data coordinated with the findings showing that bacitracin induced a non-significant elevation in phagocytic activity and phagocytic index (Adel 2018).…”
Section: Discussionmentioning
confidence: 99%